Attacking the profits of crime : drugs, money and laundering (UN Office for Drug Control and Crime Prevention ViennaAT, 1998)
Considers the subject of money-laundering and its impact on the world's financial systems and financial markets. Looks at the way governments try to regulate those markets and the institutions that drive them. Considers what steps may be needed to make life much more difficult for anyone who tries to launder money.
Panel discussion held at the United Nations, New York on 10 June 1998